Exploring the Integration of Artificial Intelligence in High School Education: Challenges, Opportunities, and Future Directions - Made Wira Yanottama; Ketut Agustini; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2026)
The rapid development of educational technology has not been fully accompanied by the readiness to integrate Artificial Intelligence (AI) into learning processes at the secondary school level. Limitations in digital literacy, infrastructure, and pedagogical competence remain the main challenges in optimizing the use of AI. This study aims to analyze the forms of integration, challenges, opportunities, and future directions of AI implementation in learning. This study employed a Systematic Literature Review (SLR) method guided by the PRISMA framework. Data were collected through a search of articles in the Scopus and Google Scholar databases, focusing on publications from 2020 to 2025, resulting in 20 relevant articles for analysis. Data analysis techniques involved identification, selection, synthesis, and interpretation of research findings. The results indicate that AI integration in learning includes the use of chatbots and generative AI, adaptive learning, intelligent tutoring systems, and learning analytics integrated with Project-Based Learning models. The main challenges include limited infrastructure, teacher readiness, low digital literacy, and ethical issues such as algorithmic bias and data privacy. On the other hand, AI offers significant opportunities to enhance personalized learning, learning motivation, creativity, and 21st-century skills. Therefore, comprehensive implementation strategies are needed to optimize the role of AI in transforming learning practices.